The socio-ecological determinants of change in school travel mode over the transition from childhood to adolescence and the association with physical activity intensity. (November 2021) - Irwin, Jessica; van Sluijs, Esther M.F.; Panter, Jenna; Jones, Andy
Abstract: School active travel contributes to young people's physical activity levels, yet the prevalence is low, and declines with age. Based on determinants from the social-ecological model we investigated changes in school travel behaviour over the transition from childhood to adolescence in participants from the baseline and four-year follow-up of the SPEEDY cohort. Descriptive analysis examined how travel behaviours changed and were related to physical activity. Multinomial logistic regression investigated determinants. Some 38% of participants changed travel mode; 66% from active to passive. Passively traveling participants at follow-up showed a decrease in physical activity. Several social-ecological domains were associated with change. Findings suggest multicomponent interventions are required to support active travel in youth. Highlights: Active travel to school is a key contributor to young people's activity levels. Many children change travel mode during the transition to adolescence. Taking up a passive travel mode leads to a decline in physical activity levels. Many different domains of a young person's life influence change in travel mode. An intervention targeting many domains of life may increase levels of active travel.